The Impact of Corporate Culture on Marketing Performance - Muhammad Anwar Fathoni; Ahmad Rodoni (Ekonomi Syariah IAIN Kudus, 2018)
ABSTRACT The purpose of this study is to determine the typology of corporate culture of Islamic banking. This study also aims to determine the influence of corporate culture of Islamic banking on marketing performance.This study proves that the corporate culture of Islamic banking that accommodates the Islamic teaching has influence on marketing performance.This study is a comparative study between Bank Muamalat and BNI Syariah. Mixed method is used in this study to analyze collected data. The primary data obtained through survey and interview with employees of the Islamic bank. While secondary data obtained from the annual report documentation, books and articles in scientific journals and other sources that relevant to the research. Keywords: Corporate Culture, Marketing Performance, Islamic Banking